Determination of uruf rate of gold jewelery in the state of Sarawak - Omar, Sharifah Anom; Abd Latif, Mohd Syahiran; Bujang, Saimi; Mat Rani, Mohd Afandi; Magiman, Mohamad Maulana; Pg Musa, Pg Ismail; Nordin, Mohd Norazmi (Wolters Kluwer Health, 2022)
Gold is a very precious metal and has a high value. Gold zakat is one of the property zakat that is obligatory to be paid by Muslims. However, the zakat on gold jewelry requires the determination of the uruf rate to enable the zakat to be paid. The need to determine the uruf rate of gold jewelery in the state of Sarawak is necessary because to identify the latest uruf rate in society. The study was conducted on 538 Muslim women respondents throughout the state of Sarawak. This study uses a quantitative method by using a structured interview form (structured interview) or standardized (standardized) face to face (face to face) to obtain information and data from respondents.